Large‐Scale Intrusion of Circumpolar Deep Water on Antarctic Margin Recorded by Stylasterid Corals - King, Theresa M.; Rosenheim, Brad E.; Post, Alexandra L.; Gabris, Theresa; Burt, Taylor; Domack, Eugene W. (Paleoceanography and Paleoclimatology, 2018)
We present centennial‐scale radiocarbon (14C) records archived by deep sea stylasterid corals from the outer shelf and upper slope of the Antarctic margin. These novel stylasterids (Errina spp.) were collected from the western Ross Sea shelf (500 m) and slope (1,700 m), as well as the eastern Wilkes Land shelf (670 m). We provide two corals from each region and document an abrupt reversal of 14C ages in the upper (younger) part of each coral. We test the statistical robustness of each record and demonstrate the significance of the age reversals, as well as the ability of these corals to record environmental change. We discuss a variety of possible drivers for this 14C reversal and conclude that it is most likely an encroachment of 14C‐depeleted Circumpolar Deep Water (CDW). This water mass has regionally intruded onto the Antarctic margin in recent decades, facilitating loss of grounded Antarctic ice; which has implications for global sea level, deep‐water formation, and carbon sequestration in the Southern Ocean. Thus, understanding the past variability of CDW on the margin is vital to better constrain climate change trajectories in the near future. We estimate large‐scale encroachment of CDW onto the shelf likely commencing after 1830 CE (±120 year). We present possible drivers for the intrusion, but highlight the need for additional chronologic constraint. This study not only demonstrates the utility of a novel coral taxon but also presents the paleoceanographic community with a testable hypothesis concerning a recent, widespread CDW intrusion.